Antegrade scrotal sclerotherapy of internal spermatic veins for varicocele treatment: technique, complications, and results - Alessandro Crestani; Gianluca Giannarini; Mattia Calandriello; Marta Rossanese; Mariangela Mancini; Giacomo Novara; Vincenzo Ficarra (Asian Journal of Andrology, 2016)
Varicocele repair is mainly indicated in young adult patients with clinical palpable varicocele and abnormal semen parameters. Varicocele treatment is associated with a significant improvement in sperm concentration, motility, morphology, and pregnancy rate. Antegrade scrotal sclerotherapy (ASS) represented one of the main alternatives to the traditional inguinal or suprainguinal surgical ligation. This article reviews the use of ASS for varicocele treatment. We provide a brief overview of the history of the procedure and present our methods used in ASS. In addition, we review complication and success of ASS, including our own retrospective data of treating 674 patients over the last 17 years. Herein, we analyzed step by step the ASS technique and described our results with an original modified technique with a long follow-up. Between December 1997 and December 2014, we performed 674 ASS. Mean operative time was 14 min (range 9 to 50 min). No significant intraoperative complications were reported. Within 90 days from the procedure, postoperative complications were recorded in overall 49 (7.2%) patients. No major complications were recorded. A persistent/recurrent varicocele was detected in 40 (5.9%) cases. In 32/40 (80%) cases, patients showed preoperative grade III varicoceles. In patients with a low sperm number before surgery, sperm count improved from 13 × 10 6 to 21 × 10 6 ml−1 (P < 0.001). The median value of the percentage of progressive motile forms at 1 h improved from 25% to 45% (P < 0.001). Percentage of normal forms increased from 17% before surgery to 35% 1 year after the procedure (P < 0.001). In the subgroup of the 168 infertile patients, 52 (31%) fathered offspring at a 12-month-minimum follow-up. Therefore, ASS is an effective minimal invasive treatment for varicocele with low recurrence/persistence rate.